Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s11427-021-1997-2
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for increasing the yield of stem cell-derived exosomes: what factors may be involved?

Abstract: Exosomes are nano-scale extracellular vesicles secreted by cells and constitute an important part in the cell-cell communication. The main contents of the exosomes include proteins, microRNAs, and lipids. The mechanism and safety of stem cell-derived exosomes have rendered them a promising therapeutic strategy for regenerative medicine. Nevertheless, limited yield has restrained full explication of their functions and clinical applications To address this, various attempts have been made to explore the up- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 171 publications
(196 reference statements)
0
16
0
Order By: Relevance
“…Although MSC-Exos were promising therapeutic agents, the research on the efficacy of MSC-Exos on bone regeneration is still in its infancy. Numerous in vitro trials have demonstrated the effectiveness of MSC-Exo in bone disease, ( Feng et al, 2021b ), while most experiments in vivo have been conducted on small animals (including rats, mice and rabbits), validating the effectiveness of MSC-Exo on bone regeneration in animal models of bone defects and diseases such as osteonecrosis and osteoporosis ( Tan et al, 2020 ), supporting the basis for clinical translation of MSC therapeutic agents ( Ren et al, 2022b ). However, the clinical trials of MSC-Exo is still limited.…”
Section: Future Perspectivesmentioning
confidence: 97%
“…Although MSC-Exos were promising therapeutic agents, the research on the efficacy of MSC-Exos on bone regeneration is still in its infancy. Numerous in vitro trials have demonstrated the effectiveness of MSC-Exo in bone disease, ( Feng et al, 2021b ), while most experiments in vivo have been conducted on small animals (including rats, mice and rabbits), validating the effectiveness of MSC-Exo on bone regeneration in animal models of bone defects and diseases such as osteonecrosis and osteoporosis ( Tan et al, 2020 ), supporting the basis for clinical translation of MSC therapeutic agents ( Ren et al, 2022b ). However, the clinical trials of MSC-Exo is still limited.…”
Section: Future Perspectivesmentioning
confidence: 97%
“…The nanosized EVs can be secreted from almost all existing cell types ( Kucuk et al, 2021 ; Wang et al, 2022 ), and they participate in cell–cell communication ( Feng et al, 2021 ; van Niel et al, 2022 ). In a study of the EVs spontaneously flowing between non-stem cancer cells and cancer stem cells (CSC), tumors were shown to adapt and thrive depending on a cellular collaboration network mediated by EVs secreted from the CSC ( Ruivo et al, 2022 ).…”
Section: Functional Communication At the Cell Levelmentioning
confidence: 99%
“…The presence of EVs in the extracellular space was identified in 1980 [ 3 ]. However, the secretion of EVs was initially seen as a form of secreting unwanted proteins or cellular waste resulting from either cellular damage or homeostasis [ 4 , 5 ]. In the mid-1990s, EVs were shown to induce vital immune responses, and in the last decade, with the advance of research methods and techniques, numerous studies have identified EVs as significant mediators in cell–cell communication [ 6 ].…”
Section: Introductionmentioning
confidence: 99%